Sleep, sedentary behavior, physical activity and associated factors among Brazilian adolescents - Costa, Bruno Gonçalves Galdino da (2020)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2020.